Avaliação neuropsicológica em crianças com distrofia muscular deDuchenne, acompanhadas no ambulatório de doenças neuromusculares doHospital das Clínicas da Universidade Federal de Minas Gerais - Maria do Carmo Mangelli Ferreira de Araujo (2010)
Objective: to revise the literature on the neuropsychological evaluation and presence of ADHD in children and young adults with Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) and the correlation between cognitive functions and genetic factors. Source of data: A nonsystematic bibliographic review, for the period 1966-2010, using PubMed/MEDLINE and LILACS database using the following search terms: Duchenne muscular dystrophy, Becker muscular dystrophy, neuropsychological assessment, deletion of Dystrophin gene and Attention Deficit/Hyperactivity Disorder. Summary of data: Neuropsychological evaluation of DMD/DMB children young adults reveals variable degrees of cognitive impairment with mental retardation in approximately 20-30% of patients. The verbal intelligence quotient (VIQ) is more affected in children and young adults with DMD/DMB. DMD/DMB patients had higher incidence of ADHD than the general population. Several studies point to relationship between the cognitive deficit and genetic aspects of these children and young adults, but such data are not conclusive. Conclusion: neuropsychological assessment of DMD/DMB patients is an useful tool in the clinical evaluation, allowing to define the cognitive profile of each child. This information provides information for better driving individualized psychoeducation improving quality of life and social integration of these patients.